Second Culture and Second Nature: Fact, Post-Fact, and the Social Construction of Scientific Objects - Russell, Conrad (Sociologija. Mintis ir veiksmas, 2017)
The use of constructionism by climate change deniers and ‘9-11 truthers’ to support ‘post-fact’ arguments in recent political and social debates has created controversy within science studies. Here, I seek to re-evaluate what constructionists actually say about facts in science. Through revisiting Gaston Bachelard – a key influence on scientific constructionism – I argue that science can penetrate to the ‘noumenal core’ of the phenomena it studies because it constructs them. This, however, need not imply that facts can be whatever we want them to be.
Keywords: facts; social construction; artefacts; epistemology